2018
DOI: 10.1080/10376178.2018.1501276
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nursing students’ attitudes toward older people

Abstract: This study found that nursing students' attitudes toward older people were positive. Cultural features of the region where the study was conducted are considered to have effects on this result. Impact statement: As nursing students will provide care to older people in the future, it is important to know and assess their attitudes towards the older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The few studies that have been published on nursing students in Spanish universities provide data indicating slightly positive scores [ 37 , 38 ]. The scores obtained were similar to those obtained in other studies on nursing students in Europe and the United States [ 39 , 40 , 41 ], and slightly higher than in Asian students [ 42 ]. The cultural background seems to be an important factor, as other studies have also reported more negative scores in Asian countries compared to western countries [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…The few studies that have been published on nursing students in Spanish universities provide data indicating slightly positive scores [ 37 , 38 ]. The scores obtained were similar to those obtained in other studies on nursing students in Europe and the United States [ 39 , 40 , 41 ], and slightly higher than in Asian students [ 42 ]. The cultural background seems to be an important factor, as other studies have also reported more negative scores in Asian countries compared to western countries [ 43 ].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies in the literature revealed similar results. [7,26,27] The study suggest that the adoption of the belief that the elderly should be respected depending on the cultural significance of aging in the Turkish society and the region where the study was conducted is effective in reducing discrimination.…”
Section: Discussionmentioning
confidence: 98%
“…Empathic tendency in nurses is gaining importance in order to remove the attitudes that increase ageism and to increase the quality of care. [7,8] The empathic tendency is defined asthe willingness to understand and help another person. [9,10] Empathic tendency, which expresses the possibility of developing empathy, is an innate trait, developed by training and it renders the development of empathic attitude of an individual obligatory by creating the emotional dimension of empathy.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it adopts an institutional point of view and includes lots of items which consider the elderly person as a resident. Nursing students' attitudes towards gerontological nursing have been studied using Kogan's KAOP instrument (Kogan, 1961), which has been applied in several international studies (e.g., Bakan et al., 2018; Salin et al., 2020; Söderhamn, et al., 2001). In a previous study, we found gerontological nursing to require a wide range of competencies, such as skills related to caring for, interacting with, and promoting health and well‐being among older people, along with clinical and ethical competence (Tohmola et al., 2020).…”
Section: Introductionmentioning
confidence: 99%